A systematic review of the literature reporting on randomised controlled trials comparing treatments for faecal incontinence in adults. Issue 1 (2nd January 2019) - Lal, Nikhil; Simillis, Constantinos; Slesser, Alistair; Kontovounisios, Christos; Rasheed, Shahnawaz; Tekkis, Paris P.; Tan, Emile
Abstract: Aim: To perform a review of the literature reporting on randomised controlled trials (RCTs) comparing treatments for faecal incontinence (FI) in adults. Methods: A literature search of MEDLINE, Embase, Science Citation Index Expanded and Cochrane was performed in order to identify RCTs reporting on treatments for FI. Results: The review included 60 RCTs reporting on 4838 patients with a mean age ranging from 36.8 to 88 years. From the included RCTs, 32 did not identify a significant difference between the treatments compared. Contradictory results were identified in RCTs comparing percutaneous posterior tibial nerve stimulation and transcutaneous tibial nerve stimulation versus sham stimulation, biofeedback-pelvic floor muscle training (BF-PFMT) versus PFMT, and between bulking agents such as PTQ TM versus Durasphere ® . In two separate RCTs, combination treatment of amplitude-modulated medium frequency stimulation and electromyography-biofeedback (EMG-BF), was noted to be superior to EMG-BF and low-frequency electrical stimulation alone. Combination of non-surgical treatments such as BF with sphincteroplasty significantly improved continence scores compared to sphincteroplasty alone. Surgical treatments were associated with higher rates of serious adverse events compared to non-surgical interventions. Conclusions: The current evidence has not identified significant differences between treatments for FI, and where differences were identified, the results were contradictory between RCTs.